AI Awareness, Facilitating Factors, Perceived Risk, Attitude Toward AI, Behavior Toward AI, AI Application and Ethical Concerns: A Study of Higher Education Institutions (Journal of Social Sciences Review, 2025)
AI is one of the most significant trends in the modern world, and it changes industries and redesigns people's lives and occupations. This research aims to establish attitudes and behavior toward AI using 439 finalized samples of instructors in academic institutions in Multan, Pakistan. Key variables like AI awareness level, facilitating factors, perceived risk, and ethical concerns were tested for the application of AI. The results show that AI awareness, the facilitating factors, and perceived risks impact attitudes towards AI. A positive attitude predicts AI-related behavior, which is a key determinant of AI application in educational institutions. However, ethical concern plays a non-significant role in the relationship between behavior and AI application, suggesting that it may not have a direct influence on the adoption of AI from this perspective. This paper highlights the necessity of an awareness campaign and the establishment of conducive conditions for AI use. Some of the limitations include the cross-sectional study design and the geographical location of the participants, which may affect the generalization of the findings. Future research will need to include longitudinal designs, different populations, and other social psychological factors like trust, emotions, and norms to investigate AI adoption patterns further.
Keywords: Artificial Intelligence; AI Adoption; AI Awareness; Facilitating Factors; Perceived Risk; Attitude Toward AI; Behavior Toward AI; AI Application; Ethical Concerns